Incorporation of self-referenced beliefs process in adolescents that have lived in a vulnerable social situation - Loos, Helga (2014)
The purpose of this work is to investigate the interaction betweena group of self-referenced beliefs and the strategies used to copewith, and eventually overcome, the adversity in adolescents thatlived in a situation of social vulnerability. According to this goalfour instruments were used: The Rosenberg Self-Esteem Scale(1965), the Piers-Harris Self-Concept Scale (1984), BanduraSelf-Efficacy Scale for Children and Adolescents (1990) and aninterview elaborated specifically for this study. The participants were 25 male adolescents from 15 to 18 years old that aresheltered in a NGO in the metropolitan region of Curitiba, Paraná. The results informed that most of these adolescents have amiddle level of self-esteem, a positive self-concept and also apositive self-efficacy. The study of particular cases emphasizesthe prominent role of these beliefs in coping with adversity andin eventual resilience processes.